Pengaruh Kualitas dan Harga terhadap Keputusan Pembelian BIODIESEL30 (Studi pada Konsumen Biodiesel 30 SPBU PT. Pertamina Wilayah Kerja Kecamatan Medan Amplas) - Sibarani, Doni; Marpaung, Nicholas (Regress: Journal of Economics & Management, 2023)
There is a threat of scarcity of fossil fuels, especially diesel fuel, which are non-renewable. Biodiesel30 fuel with 30% of its ingredients is vegetable oil and 70% fossil can be an alternative but in the distribution process it has started gradually since it was decided to replace pure diesel in 2019. Its existence is still questionable whether it is capable both in terms of quality and price to replace pure diesel especially biodiesel consumers30 PT. Pertamina working area of Medan sandpaper sub-district. This study aims to analyze the effect of product quality and price simultaneously on consumer purchasing decisions for B30 fuel at PT. Pertamina working area of Medan Amplas District. The form of research used in this research is quantitative research with an associative approach. The results of this study indicate that product quality variables (X1) and variables (X2) affect employee performance. The adjusted R square value indicates that the product quality and price variables contribute 39.3% to the purchasing decision variable. The conclusion in this study is that the product quality variable (X1) influences purchasing decisions, price (X2) influences purchasing decisions, and product quality variables (X1) and price (X2) simultaneously influence purchasing decisions.